2019
DOI: 10.1111/jnc.14656
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammation down‐regulates alpha‐synuclein expression in enteric neurons

Abstract: The protein alpha‐synuclein whose expression is strongly implicated in Parkinson's disease (PD) is not only expressed in the CNS but also in the enteric nervous system (ENS). The growing body of evidence suggesting that gastrointestinal inflammation is involved in the development of PD led us to investigate the effects of inflammation on alpha‐synuclein expression in primary culture of rat ENS and in mice with dextran sulfate sodium‐induced colitis. Using western blot and qPCR, we found that both lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
1
21
1
Order By: Relevance
“…Although we identified an elevated amount of alphasynuclein in colonic samples from patients with CD, we were unable to find any pathological changes such as phosphorylation and aggregation known to be associated with PD [43]. In addition, two independent studies performed in both acute and chronic DSS-treated mice found that intestinal inflammation was not associated with any increase in alpha-synuclein expression and phosphorylation [34,44] and we recently showed that alpha-synuclein in enteric neurons was transcriptionally downregulated by acute inflammation via a p38 signaling pathway [44].…”
Section: How Gi Inflammation May Influence the Development Of Pd?mentioning
confidence: 99%
“…Although we identified an elevated amount of alphasynuclein in colonic samples from patients with CD, we were unable to find any pathological changes such as phosphorylation and aggregation known to be associated with PD [43]. In addition, two independent studies performed in both acute and chronic DSS-treated mice found that intestinal inflammation was not associated with any increase in alpha-synuclein expression and phosphorylation [34,44] and we recently showed that alpha-synuclein in enteric neurons was transcriptionally downregulated by acute inflammation via a p38 signaling pathway [44].…”
Section: How Gi Inflammation May Influence the Development Of Pd?mentioning
confidence: 99%
“…The growing body of evidence suggesting that GI inflammation is involved in the development of PD recently led us to investigate the effects of inflammation on alphasynuclein expression in primary culture of rat ENS (23). We showed that two of the proinflammatory cytokines that are elevated in CD ( Figure S1), namely TNF-α and IL-1β, induced a downregulation of alpha-synuclein expression at both mRNA and protein levels in enteric neurons (23). Similar findings were observed when tau mRNA and protein were analyzed (our unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Primary cultures of rat ENS were generated and cultured as previously described (23). Cells were treated with 10 µM sulforaphane or MG132 (both from Sigma, Saint-Quentin-Fallavier, France) for 12h.…”
Section: Primary Culture Of Rat Ensmentioning
confidence: 99%
“…Additionally, aSyn expression, but not its pathologic aggregation, is increased in the ENS of patients with Crohn's disease (Prigent et al, 2019b) and inoculation of aSyn fibrils in the GIT is associated with an increased expression of inflammatory mediators in intestinal tissues (Challis et al, 2020). However, by contrast, it was seen that acute inflammatory stress inhibits aSyn expression in primary enteric neurons (Prigent et al, 2019a). Interestingly, inflammatory parameters, pathological aSyn aggregation and motor deficits were demonstrated to be regulated by microbiota in aSyn overexpressing mice (Sampson et al, 2016).…”
Section: Asyn In the Gastro-intestinal System: Pathological Implicationsmentioning
confidence: 99%